The Effect of Work Environment Management at DUDI on the Behavior and Work Culture Changes of Students at SMKN 1 Beji - Wijaya, Anthoni Dwi; Suyanto, Suyanto; Faizin, A. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of work environment management in the Business and Industry World (DUDI) on changes in the behavior and work culture of students at SMKN 1 Beji Pasuruan. The industrial work environment plays a key role in shaping students' professional attitudes, discipline, responsibility, and work habits, especially through industrial practice activities. This research uses a quantitative approach with a survey method. The respondents of the study are students of SMKN 1 Beji Pasuruan who have participated in industrial practice at the school's partner DUDI. Data were collected using a structured questionnaire developed based on the indicators of work environment management, work behavior, and work culture. Data analysis was performed using descriptive and inferential statistics to determine the magnitude of the influence between variables. The results of the study show that work environment management in DUDI has a positive and significant effect on changes in students' behavior and work culture. A well-managed work environment can enhance students' discipline, responsibility, cooperation, and professional attitudes. These findings emphasize that DUDI plays an important role in shaping students' work ethics to align with the needs of the workforce.